In defense of ignorance - Shapiro, Karl (Random House, 1960)
Essays by a poet and critic in which he bewails obscurity in modern verse and questions the laurels heaped on Yeats, Pound, and Eliot.
Keywords: Geschichte 1900-2000; Poetry, Modern -- 20th century; Criticism